Bacterial community assemblages in sediments under high anthropogenic pressure at Ichkeul Lake/Bizerte Lagoon hydrological system, Tunisia. (September 2019) - Ben Salem, Fida; Ben Said, Olfa; Cravo-Laureau, Cristiana; Mahmoudi, Ezzeddine; Bru, Noëlle; Monperrus, Mathilde; Duran, Robert
Abstract: Bacterial communities inhabiting sediments in coastal areas endure the effect of strong anthropogenic pressure characterized by the presence of multiple contaminants. Understanding the effect of pollutants on the organization of bacterial communities is of paramount importance in order to unravel bacterial assemblages colonizing specific ecological niches. Here, chemical and molecular approaches were combined to investigate the bacterial communities inhabiting the sediments of the Ichkeul Lake/Bizerte Lagoon, a hydrological system under anthropogenic pressure. Although the microbial community of the Ichkeul Lake sediment was different to that of the Bizerte Lagoon, common bacterial genera were identified suggesting a lake-lagoon continuum probably due to the hydrology of the system exchanging waters according to the season. These genera represent bacterial "generalists" maintaining probably general biogeochemical functions. Linear discriminant analysis effect size (LEfSe) showed significant differential abundance distribution of bacterial genera according to the habitat, the pollution type and level. Further, correlation analyses identified specific bacterial genera which abundance was linked with pesticides concentrations in the lake, while in the lagoon the abundance of specific bacterial genera was found linked with the concentrations of PAHs (Polycyclic aromatic hydrocarbons) and organic forms of Sn. As well, bacterial genera which abundance was not correlated with the concentrations of pollutants were identified in both lake and lagoon. These findings represent valuable information, pointing out specific bacterial genera associated with pollutants, which represent assets for developing bacterial tools for the implementation, the management, and monitoring of bioremediation processes to mitigate the effect of pollutants in aquatic ecosystems. Graphical abstract: Image 1 Highlights: Evidence of bacterial continuum in Ichkeul Lake/Bizerte Lagoon. The lake and the lagoon have specific bacterial assemblages. Each type of pollutant is associated with specific bacterial genera. Uncontaminated sediments have also specific bacterial genera. Potential to develop tools for managing bacterial resources.